Adolescent Reproductive Health Education Needs Analysis as a Foundation for Developing Participatory Learning Strategies: A Community Education Perspective - Hasanah, Viena Rusmiati; Maslihah, Sri; Kamarubiani, Nike; Yasepta, Rengky (Journal of Nonformal Education, 2026)
Background - Adolescent reproductive health education is essential for strengthening health literacy, responsible decision-making, and healthy behavior. However, adolescents’ educational needs vary according to their social conditions, parenting patterns, perceptions of reproductive health, peer relationships, and information and media environments.Research Urgency -  Reproductive health education should be based on adolescents’ actual needs to ensure that learning content and strategies are relevant to their characteristics and lived experiences. Knowledge-centered approaches alone are insufficient to address social influences, peer pressure, and exposure to digital information. Therefore, needs assessment is essential for developing contextual and participatory reproductive health education within Community Education.Research Objectives - This study aims to analyze adolescents’ reproductive health education needs based on social conditions, parenting patterns, perceptions of reproductive health, and social and media environments as a foundation for developing participatory learning within Community Education.Research Method - A descriptive quantitative approach with a needs assessment survey design was employed. The study was conducted in Babakan Sari Urban Village, Bandung City, involving 45 adolescents selected through purposive sampling. Data were collected using a structured questionnaire subjected to expert review and readability testing. Data were analyzed using descriptive statistics, including frequencies, percentages, and cross component synthesis.Research Findings - The findings indicate that adolescents possess positive strengths, including the ability to choose friends, reject negative invitations, and demonstrate normative perceptions of reproductive health. However, they also experience diverse social and family conditions and exposure to sexual information and content through media. Thus, their educational needs extend beyond knowledge acquisition to reproductive health literacy, reflection and situational assessment, communication, decision-making, and managing peer and media influences. The synthesis produced a needs map for adolescent reproductive health education as a basis for contextual, interactive, and participatory learningResearch Conclusion - Needs assessment is a fundamental stage in developing adolescent reproductive health education. Integrating individual, family, peer, and social-media dimensions provides an empirical basis for designing participatory learning responsive to adolescents’ characteristics and contexts.Research Novelty/Contribution - This study contributes by positioning needs assessment as the starting point for participatory reproductive health learning within Community Education, providing an empirically grounded needs map for educators, families, schools, program managers, and policymakers.